MANAJEMEN PENGEMBANGAN MUTU SEKOLAH MENENGAH KEJURUAN SWASTA DALAM PENINGKATAN KEUNGGULAN BERSAING - Tuti Indriyani (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
The objectives of this research are to find the reasons of the Private Vocational High School implementing the mangement of quality development to improve the competitive excellence, the factors of the success of the implementation of management of quality development, and the contributions of management of quality development in impoving the competitive excellence by using case study at three private vocational high school in Jambi of SMK S Yadika Kota Jambi, SMK S Attaufiq Kota Jambi and SMK S Dharma Bhakti 4 Kota Jambi. The results of this study show that the three SMK S show the implementation of management of quality development, therefore, they are able to compete. There is religion contents which is given and solid teamwork and responsibility. The factors of the success are able to improve the competitive excellence are a good management which is supported by qualified human resources, good relationship with the workplace, and well-planned policies. The contributions of quality development management towards the achievement that is achieved by the SMK S in improving the competitive excellence are the existence of the quality assurance which runs the responsibility and right well, management responsibility, determining work standard, and local and global excellence-based education. In conclusion, the implementation of management of quality development at SMKs  has been able to make the school has good quality that can increase the competitive excellence in Jambi province.